P5-S6.22 Social-structural factors associated with supportive service use in a cohort of HIV-positive individuals on ARV therapy in British Columbia, Canada. (10th July 2011) - O'Brien, N; Palmer, A K; Zhang, W; Michelow, W; Shen, A; Roth, E; Rhodes, C L; Montaner, J S G; Hogg, R S
Abstract : Introduction: Medical services are seldom the only assistance required for HIV-positive individuals to lead longer, healthier lives. The clinical complexities of HIV infection and the multiple needs of people living with HIV often require additional assistance to ensure optimal health outcomes. Supportive services (eg, housing, food, counselling, addiction treatment) are increasingly conceptualised as critical components of care. Our study investigates social and clinical correlates of supportive service use across differing levels of engagement. Abstract P5-S6.22 figure 1 presents the conceptual model of the study. Methods: The Longitudinal Investigations into Supportive and Ancillary Health Services (LISA) is a cross-sectional cohort of HIV-positive persons on antiretroviral therapy in British Columbia, Canada. Interviewer-administered surveys collected information regarding sociodemographic factors, substance use, social support networks, and supportive services. Clinical variables were obtained through longitudinal linkages with the Drug Treatment Program at the BC Centre for Excellence in HIV/AIDS. Participants were stratified by level of service engagement (daily, weekly, and 1–3 months). Bivariate analysis and a logistic regression proportional odds model were used to identify variables significantly associated with supportive service use. Results: Among 915 participants, 742 (81%) reported using supportive services, of which 344 were highly engaged, 280 moderately engaged, and 118 minimally engaged. Food programs, medication support, and counselling and social supports groups were services most accessed. Multivariate results demonstrated that those most engaged in supportive services were more likely to report poor social determinants of health such as low income [adjusted OR (AOR)=1.81]; not having completed high school (AOR=1.97); unstable housing (AOR=1.89); and current illicit drug use (AOR=1.60). After adjusting for social determinants, there were no significant differences in clinical measures across different levels of engagement with supportive services. Conclusion: High service use by those demonstrating social and clinical vulnerabilities reaffirms the need for continued expansion of supportive services to facilitate a more equitable distribution of health among persons living with HIV.